Teaching and Learning in Industries: Are We Malaysian Workers Really Ready for the E-Training - Hasmadi, Hassan (Penerbit UTHM, 2011)
E-training style requires a strong readiness level among industrial workers in order to ensure that gain its optimum advantages. The purpose of the study is to explore analytically how the demographic factors affect the computer usage attitude, computer literacy, computer facility and access technology. The study also explores analytically the e-training readiness level in terms of computer usage attitude, computer literacy, computer facility and access technology among industrial workers. Four hundreds industrial workers from electronic industries, food industries, poultry industries, and textile industries in Batu Pahat, Johore were involved in this study. The data were collected using questionnaires and were analyzed quantitatively. Through multiple regression analysis, the finding showed that some demographic factors (worker characteristics and work place)were significant at predicting the computer usage attitude, computer facility and technology access. the finding also showed that there was a high level of e-training readiness among industrial workers in the aspect of computer usage attitude. But the aspect of computer literacy, computer facility, and technology access showed only a moderate level of reediness. In general, the e-training readiness level of among industrial workers is still moderate. This situation should be overcome in order to ensure that the e-training approach has been emphasized in Malaysia Occupational Skills Development and Training Master Plan 2008-2020 would be implement successfully. Therefore, some suggestion for improvement have been presented toward enhance the e-training readiness among industrial workers.